More than a virus: a qualitative study of the social implications of hepatitis B infection in China - J. Wallace; M. Pitts; C. Liu; V. Lin; B. Hajarizadeh; J. Richmond; S. Locarnini (BMC, 2017)
Abstract Background China has the largest absolute number of people living with hepatitis B with up to 300,000 people estimated to die each year from hepatitis B related diseases. Despite advances in immunisation, clinical management, and health policy, there is still a lack of accessible and affordable health care for people with hepatitis B. Through in-depth interviews, this study identifies the personal, social and economic impact of living with hepatitis B and considers the role of stigma and discrimination as barriers to effective clinical management of the disease. Methods Semi-structured qualitative interviews were held with 41 people living with hepatitis B in five Chinese cities. Participants were recruited through clinical and non-government organisations providing services to people with hepatitis B, with most (n = 32) being under the age of 35 years. Results People living with hepatitis B experience the disease as a transformative intergenerational chronic infection with multiple personal and social impacts. These include education and employment choices, economic opportunities, and the development of intimate relationships. While regulations reducing access to employment and education for people with hepatitis B have been repealed, stigma and discrimination continue to marginalise people with hepatitis B. Conclusions Effective public policy to reduce morbidity and mortality associated with hepatitis B needs to address the lived impact of hepatitis B on families, employment and educational choices, finances, and social marginalisation.